JUAL BELI TANAH YANG DILAKUKAN TANPA AKTA PPAT: (STUDI PUTUSAN NOMOR 42/Pdt.G/2010/PN.Mtp) - Budjang, Cheri Bayuni (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
Buying and selling is a way to transfer land rights according to the provisions in Article 37 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration which must include the deed of the Land Deed Making Official to register the right of land rights (behind the name) to the Land Office to create legal certainty and minimize the risks that occur in the future. However, in everyday life there is still a lot of buying and selling land that is not based on the laws and regulations that apply, namely only by using receipts and trust in each other. This is certainly very detrimental to both parties in the transfer of rights (behind the name), especially if the other party is not known to exist like the Case in Decision Number 42 / Pdt.G / 2010 / PN.Mtp